O humor em manuais escolares de Matemática - Menezes, Luís (2017)
Humor has a wide presence in people's lives, combining affective and cognitive elements with the intention of well-being. In addition to the leisure contexts, humor has also been used in contexts associated with work, namely schools, placed at the service of teaching. Since school textbooks are a resource widely used by teachers, particularly those of mathematics, it seems pertinent to us: (I) to access the usage of humor in Mathematics school textbooks; and (ii) describe the humor used in textbooks and discuss their didactic framework. For this, we submitted, to content analysis, four textbooks of Mathematics (of the 4th and 5th grades) with wide national diffusion. The results reveal that humor, both in the text and in the illustration, has practically no expression in the textbooks. Even so, all textbooks value, at the illustration level, light-hearted situations, presenting repeatedly, people laughing.